2005
DOI: 10.1007/bf02867409
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of reference intervals in Indian population

Abstract: The central role of the laboratory scientist is to aid the clinician, in interpreting observed values, by providing relevant reference values in a convenient and practical form. In India, reference values used in laboratories have been established in the western population. But these can be questioned due to differences in genetic load, lifestyle, and diet. This review highlights the approach for establishing reference values in our population using the IFCC guidelines and our observations from our data as com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
22
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 7 publications
6
22
1
Order By: Relevance
“…9), GGT 6.76-51.09, bilirubin 0.40-1.34) as compared to females (SGOT 13-50.43, SGPT 9-63.43, GGT . These findings are consistent to finding of other workers [15][16][17]. These differences can be correlated to dietary habit, smoking and alcoholism.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…9), GGT 6.76-51.09, bilirubin 0.40-1.34) as compared to females (SGOT 13-50.43, SGPT 9-63.43, GGT . These findings are consistent to finding of other workers [15][16][17]. These differences can be correlated to dietary habit, smoking and alcoholism.…”
Section: Resultssupporting
confidence: 93%
“…12) which showed reverse trend. These findings are consistent to findings observed by other workers [15][16][17]. The increase in RI of SGPT was more pronounced in age group 20-40 years as compared to age groups 41-60 years (Fig.…”
Section: Resultssupporting
confidence: 93%
“…In the present study, RI for these biochemical parameters observed coincided with the reported RI [ Table 1]. In an another study conducted by Ashavaid et al reported lower RI for urea and Creatinine ranging from 4-35mg% and 0.7-1.3mg% respectively in individuals of Mumbai opted for BUPA Health Screening Programme [5]. The lower RI indicates preponderance of vegetarian and young individuals participating in the study.…”
Section: Resultssupporting
confidence: 88%
“…Moreover India is country with extreme seasonal variations, extreme variations in temperature, different dietary habits, life style and physical activity which could affect blood levels of several parameters. There is a need to realize, whether, there is a requirement for restructuring the reference interval for an Indian population [5].…”
Section: Introductionmentioning
confidence: 99%
“…Our findings are though consistent with studies conducted in south Indian population by Sultana et al and Ashavaid et al to the extent that upper cut off for most of the parameters was higher than the reported RI. However cut off for SGOT, SGPT and GGT in present study was lower as compared to values reported by Sultana et al [2]and Ashavaid et al [3]. The variations in findings may be attributed to differences in size and habitat (rural/urban) of reference population, dietary habits, life style and climatic conditions.…”
Section: Dear Editorcontrasting
confidence: 77%